NEW RECORDS OF CINEREOUS HARRIER Circus cinereus (ACCIPITRIDAE) IN THE HIGH ANDES OF SOUTHERN ECUADOR - Villegas, Fernando; Barros, Santiago; Landázuri, Boris; Astudillo, Pedro (Revista Ecuatoriana de Ornitología, 2022)
Cinereous Harrier Circus cinereus is a local species in Ecuador, occurring in agricultural grasslands and páramofrom north to central-south Andes. Little is known about its distribution in southern Ecuador. In this region, records are scarce and have not been adequately documented. We present the first video record of an adult female and a sighting of an adult male in the páramoof Quimsacocha National Recreation Area, Azuay province, southwest Ecuador. Our findings suggest that C. cinereus may be locally distributed further south of the currently known distribution and that it prefers open habitats, particularly cushion páramo, wetlands, and marshes in the high Andes and humid inter-Andean valleys.
Keywords: cushion vegetation, páramo ecosystem, raptor, Quimsacocha National Recreation Area, video record.